ORIENTALIS DAN ORIENTALISME DALAM PERSPEKTIF SEJARAH - Akkase Teng, Muhammad Bahar (Universitas Hasanuddin, 2016)
elaborated. The study of the orientalism is very complex (easterm affairs, particularly Islam)which is brought about by the motifs such as religious, scientific, economical, andpolitical matters.The terms orientalists and orientalism appeared in Andalusia (Spain) in the seventhcentury (Hijriah/ Islamic calender) or fourteenth century (AD) . They gnawed Islam byimmersing the moslems into the misieading school of thoughts primarily the younggeneration by turning them away from their religion with the teachings ofmaterialism, and secularism.The orientalism development phases are : (1) the missionary and anti Islamstarted in the sixteenth century (AD) . (2) the studies and distribes were in the seventeenth and eighteenth centuries, (3) studies and colonialisms were in the nineteenth century andthe first quarter of the tweentieth century (AD). (4) the study and politics were in thesecond half of the nineteenth century (AD). The main objective of the orientalisms is todisclose and reveal the symbolic significances of the profound Islamic Culturalexpressions, in which the Arabic language represents the primary medium.Key words : Orientalism, development, objective, history